Site com conteúdo apropriado à web semântica e mecanismos de busca - Leme, Luciano Gonzaga (2009)
This work introduces an approach which main purpose is to ask and present possible ways so that the web site s content will be appropriately offered related to Semantic Web and Search Engines. To achieve this purpose many researches were made and used the author s experience in this area. Therefore many concepts and technologies were combined and used, such as: metadata, ontologies, semantic web services and search engine optimization. Metadata allow qualifying informations appropriately, ontologies are used to improve domain s analysis problem and to obtain software components with semantic descriptions, which may be reused in a great variety of applications. Semantic web services may be used as software components spread through the Internet to perform applications complex tasks. Starting asking what should be published in a web site, or even better, how should be a web site s content the work exposes knowledges and technologies to answer the question: how to offer appropriated content? After exposing the associated concepts and showing possible solutions a conclusion is achieved with questions and possible researches which will allow appropriated content sites development with Semantic Web and its possible positive collateral effects, granting improvement in both: knowledge utilization and available informations in the web